Wildfire - Oldham, Nick, 1956- (Oldham, Nick, 1956- Detective Superintendent Henry Christie novel, 2020)
"Henry Christie is enjoying a quiet retirement running the Tawny Owl pub - until a devastating moorland fire tears through the surrounding area and he finds himself at the forefront of coordinating the local response. When the occupants of a remote farm can't be contacted, Henry goes to check on them - and makes a grisly discovery. Reluctantly agreeing to help the police with their investigation, Henry is reunited with DC Diane Daniels, and is soon confronting an explosive mix of organized crime, violence and drug turf wars which leads him back to his old hunting ground in Blackpool - and old enemies who will stop at nothing to finally have their revenge."--Provided by publisher.